INFLUENCE OF GAMMA IRRADIATION ON THE GROWTH, PHOTOSYNTHESIS AND PHENOLIC CONTENT OF BASIL (OCIMUM SANCTUM L.) - Abello, Nonna Fatima H; Enojada, Grace R; Pascual, Pet Roey L (Journal of Agriculture and Technology Management; Vol 23 No 2 (2020): Vol 23 No 2 (2020): Journal of Agriculture and Technology Management (JATM) Volume 23 July - December 2020 Issue, 2020)
Basil is an aromatic herb commonly used as medicine by many. Its different parts like leaves, stem, flower, root, and seeds are used for different purposes. Phenols are secondary metabolites that play an important role as plant-derived medicinal compounds and these mostly have low quantity on plants, like in Basil. High- energy electromagnetic radiation is highly used and an effective method to induce mutation and enhance secondary metabolite production in plants. Basil seeds were treated with 0 kGy, 0.1 kGy, 0.2 kGy and 0.3 kGy gamma irradiation. Li-Cor P6800 portable photosynthesis system was used to gather photosynthesis data. The highest dosage, 0.3 kGy, yielded the shortest plants at an average of 17±0.4SE mm. Exposure to gamma radiation also lowers the plant’s survival by 47%. On photosynthetic responses, transpiration rate decreased at -2.80 µmol H2O m -2 s -1 as the gamma dosage was increased. However, total leaf conductance to H 2 O and CO 2 increased to 0.2 kGy and 0.3 kGy at 0.01 and 0.007 mmol m⁻² s⁻¹ as the gamma dosage was increased. Plants treated with 0.3 kGy gamma radiation also showed 86% higher amounts of intercellular CO 2 (80,438.16 umol mol-1) than those not exposed to gamma irradiation. On phenolic content, the highest was those exposed to 0.2 kGy and 0.3 kGy at 200.384±5.543 mg GAE/g and 210.574±12.003 mg GAE/g, respectively. These resultant characteristics can therefore be a source of parent material for breeding.